Epidemiological perspectives of COVID-19 in Telangana and India: a descriptive study design - Barhate, Amruta; Bhatia, Prakash (International Journal Of Community Medicine And Public Health, 2021)
Background: The COVID-19 pandemic has made the world to come to a standstill. What started as on 16th March 2020, as 114 confirmed cases of COVID‑19 in the country has now reached worrisome figures. The latest world scenario as per WHO as on 30th November, 2020 is as under-World data: 62,509,444 cases, deaths: 1,458,782; USA: 13,082,877 cases, deaths: 263,946; India: 9,431,691 cases, deaths 137, 139. It is evident that worldwide India is number two in case load and there’s no reason to prevent India from becoming number one unless appropriate corrective steps are taken. Methods: The present study has looked into various data sources available in public domain. The study covered a period of almost nine months i.e., from March 2020 to November 2020. The study revealed a steady increase in the number of COVID-19 cases from March 2020 with peak of pandemic occurring in the mid of September and then a steady decline of cases from October. Results: The data analysis shows that after peaking of cases in September, the epidemic will decline in a phased manner by the end of March 2021. Even though there is a decline seen from the month of October, spike of COVID-19 cases was seen in November in some of the states of India. Therefore, we can’t deny the possibility of a second wave of pandemic to occur in the month of December 2020 and January 2021. Conclusions: Hence appropriate and strict control measures have to be put in place for effective control of the Pandemic and its resurgence.